2020
DOI: 10.3390/ma13122873
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mortar Strength in Historical Brick Masonry Using the Penetrometer Test and Double Punch Test

Abstract: This paper presents the results of the minor destructive testing of mortars in masonry structures of four buildings erected at the turn of the 19th and 20th centuries. The buildings were erected in the historical centre of Cracow. The objective of testing was to determine mortar compressive strength in masonry joints. The in situ tests were carried out with the use of a penetrometer RSM-15 with the standardised impact energy equalling 4.55 nm. Laboratory tests on mortar specimens taken from the structures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The main advantage of this test is the direct measurement of the mortar’s mechanical properties. A negative feature of this test is the high susceptibility of its result to a range of factors, such as specimen slenderness [ 16 , 17 , 18 , 19 ], a manner in which the surface is leveled [ 20 , 21 ], the shape and diameter of steel punches [ 16 ] or the presence of large aggregate grains [ 22 ]. In addition, in the case of walls with good adhesiveness between brick and mortar, extracting specimens is really difficult or even impossible.…”
Section: Minor-destructive Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of this test is the direct measurement of the mortar’s mechanical properties. A negative feature of this test is the high susceptibility of its result to a range of factors, such as specimen slenderness [ 16 , 17 , 18 , 19 ], a manner in which the surface is leveled [ 20 , 21 ], the shape and diameter of steel punches [ 16 ] or the presence of large aggregate grains [ 22 ]. In addition, in the case of walls with good adhesiveness between brick and mortar, extracting specimens is really difficult or even impossible.…”
Section: Minor-destructive Testing Methodsmentioning
confidence: 99%
“…The number of correlation functions between mortar strength acc. to DPT test ( f m.DPT ) and mortar reference strength ( f m ) is very limited, and some attempts were made in [ 16 , 22 , 23 ].…”
Section: Minor-destructive Testing Methodsmentioning
confidence: 99%
“…The acid dissolution test [17] found that the su cient ratio of lime mortar and sand mixture for the sample is 1:3 (Lime: Fine aggregate) from The mechanical characteristics of mortars rely upon the binder type and its mix ratio [18,19] addressed that in accommodating lime mortar pores, the B/A is a critical parameter and directly affects disseminating CO 2 in the lime matrix. In his ten books of architecture, Vitruvius, chapter IV [20] claimed that lime mortar of 1: 3 mix ratio is excellent for higher carbonation.…”
Section: Acid Loss Testmentioning
confidence: 99%
“…The indicator for the absolute value of the network output ( y NNi |) guarantees that each of them will be in the range of Absolute Relative Error from zero to maximum absolute Relative Error [77,78]. Consequently, it gives information about the absolute value of the maximum possible error of the mathematical model [79][80][81] represented by the already taught neural network. This criterion only includes data for the testing stage.…”
Section: The Network Structure and Its General Equationmentioning
confidence: 99%